2011
DOI: 10.3892/etm.2011.404
|View full text |Cite
|
Sign up to set email alerts
|

Dan-Shen-Yin protects the heart against inflammation and oxidative stress induced by acute ischemic myocardial injury in rats

Abstract: Dan-Shen-Yin (DSY) is a well-known traditional Chinese formula which is widely used in clinical practice for the treatment of coronary heart disease (CHD) and has produced a favorable effect in China. The present study was designed to examine whether or not acute oral DSY can protect the heart against myocardial infarction in acute myocardial ischemic rats. If so, we would then investigate the anti-inflammatory and anti-oxidant mechanisms involved. The left anterior descending coronary artery was occluded to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This adaptation process includes left ventricular dilatation, left ventricular hypertrophy, myocardial cell hypertrophy and fibrosis of the intercellular matrix. Previous pharmacological studies have indicated that numerous types of cardioprotective drugs treat cardiovascular disease via anti-inflammatory and anti-oxidant signaling pathways (4).…”
Section: Introductionmentioning
confidence: 99%
“…This adaptation process includes left ventricular dilatation, left ventricular hypertrophy, myocardial cell hypertrophy and fibrosis of the intercellular matrix. Previous pharmacological studies have indicated that numerous types of cardioprotective drugs treat cardiovascular disease via anti-inflammatory and anti-oxidant signaling pathways (4).…”
Section: Introductionmentioning
confidence: 99%
“…Dan-Shen-Yin (DSY): DSY, including sandalwood Fructus amomi and Salvia miltiorrhiza , is a famous Chinese herbal formula which is extensively used for the therapy of CHD [84, 85]. A study [86] explored whether DSY could protect from MI. The left anterior descending branch of the coronary artery was ligated to induce myocardial ischemia in rats, measuring the infarction size, inflammation factor, and antioxidative enzyme activities.…”
Section: Protective Effects Of Traditional Chinese Medicine (Tcm) mentioning
confidence: 99%
“…Gua Lou Xie Bai Ban Xia Decoction , a classical formula created by the medical sage Zhang Zhong-jing over 2000 years ago, exerts a protective effect on the ischemic rabbit myocardium, and the underlying mechanisms may involve the inhibition of nitric oxide synthase (NOS) activity and are duction in the excessive production of nitric oxide (NO) (Zhou et al, 2010 ; Zhang et al, 2011 ). Dan Shen Yin Decoction and Tao Hong Si Wu Decoction are both well-known decoctions used to treat BS with IHD (Yan et al, 2012 ; Yin et al, 2013 ; Liu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%